Strategi Kontraktor dalam Menghadapi Perubahan Cuaca yang Mempengaruhi Kemajuan Kerja - Sarpin, Norliana; Jamsari, Nurul Syafika; Sabtu@Othman, Hilyati; Ismayatim, Norddin (Research in Management of Technology and Business, 2025)
The construction industry in Malaysia has made a significant contribution to the country's economic development. In the first quarter of 2023, the industry contributed 7.4% to GDP. However, the industry faces major challenges due to weather changes, especially in Johor, where heavy rain and extreme heat are common. Therefore, this study has three main objectives: to find out which problems contractors in Johor most often face due to weather changes; to examine how weather affects construction progress; and to propose solutions to these problems. This study uses a qualitative method where data is collected through interviews with 6 respondents consisting of contractors involved in construction projects in Johor. The data obtained were analyzed using content analysis method to identify themes related to challenges, impacts, and strategies for coping with weather changes.. The results showed that the biggest challenges faced by contractors were delays in construction schedules, damage to building materials, and logistics disruptions caused by continuous rainfall. In addition, extremely high temperatures can also affect workers' health, increase labor costs, and reduce productivity. This study also found that utilizing weather forecasting technology, flexible planning, and choosing weather-resistant building materials are effective strategies to cope with these challenges. Therefore, this study was conducted to help construction contractors understand the challenges of weather changes and then develop effective strategies to ensure the smooth progress of construction projects in Johor.